2020
DOI: 10.1155/2020/2604967
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone Inhibits Hypoxic Pulmonary Hypertension through the NADPH/ROS/p38 Pathway in Adventitial Fibroblasts in the Pulmonary Artery

Abstract: Hypoxic pulmonary hypertension (HPH) is a devastating disease characterized by progressive vasoconstriction and vascular remodeling. Pirfenidone (PFD) inhibits the progression of HPH, though the molecular mechanisms remain unknown. This study is aimed at determining the role and mechanism of PFD in HPH in human pulmonary artery adventitial fibroblasts (HPAAFs), which were cultured under normal or hypoxic conditions. NOX4 and Rac1 were inhibited or overexpressed by shRNA or pcDNA3.1, respectively. Proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Pirfenidone, an anti-fibrotic agent for idiopathic pulmonary fibrosis, inhibits CAF activation and proliferation in lung and pancreatic cancers by targeting TGF-β and reduces the production of fibrotic mediators secreted by CAFs [ 114 , 115 , 116 , 117 ]. In hypoxic pulmonary hypertension, pirfenidone inhibits hypoxia-induced proliferation and migration of adventitial fibroblasts, thereby reducing the expression of α-SMA and collagen type I alpha 1 chain (COL1A1) [ 118 ]. Minnelide, a pro-drug of triptolide, downregulates TGF-β signaling in CAFs to enhance tumor regression in a mouse model of pancreatic cancer.…”
Section: Targeting Cafs For Cancer Therapymentioning
confidence: 99%
“…Pirfenidone, an anti-fibrotic agent for idiopathic pulmonary fibrosis, inhibits CAF activation and proliferation in lung and pancreatic cancers by targeting TGF-β and reduces the production of fibrotic mediators secreted by CAFs [ 114 , 115 , 116 , 117 ]. In hypoxic pulmonary hypertension, pirfenidone inhibits hypoxia-induced proliferation and migration of adventitial fibroblasts, thereby reducing the expression of α-SMA and collagen type I alpha 1 chain (COL1A1) [ 118 ]. Minnelide, a pro-drug of triptolide, downregulates TGF-β signaling in CAFs to enhance tumor regression in a mouse model of pancreatic cancer.…”
Section: Targeting Cafs For Cancer Therapymentioning
confidence: 99%
“…Indeed, hypoxia induces the proliferation and differentiation of pulmonary artery adventitial fibroblasts into myofibroblasts that ultimately, stimulate the recruitment of inflammatory cells and the release of key regulators. The proliferation and differentiation of pulmonary artery adventitial fibroblasts during chronic hypoxia are mainly dependent on the signal transduction of the p38 pathway and its downstream mediator, HIF-1 [ 66 ].…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
“…However, cck8 (Figure b) and EdU staining (Figure c,d) results showed that CeO 2 /BSA nanoclusters inhibited the proliferation of PMECs induced by hypoxia, which may be attributed to its ability of scavenging ROS. Overmigration and overproliferation coexist and influence each other in PMEC dysfunction . Hence, we also monitored the migration of PMECs treated with CeO 2 /BSA nanoclusters using a scratch test.…”
Section: Resultsmentioning
confidence: 99%